Association between ambient air pollution, meteorological conditions and exacerbations of asthma and chronic obstructive pulmonary disease in adult citizens of the town of Smederevo - Stevanovic, Ivan Miodrag; Jovašević-Stojanović, Milena; Jović-Stošić, Jamina (Vojnosanitetski pregled, 2017)
Introduction. Smederevo is the only town in Serbia with a steel factory, whose exhausts contribute to air pollution. Therefore, the city conducts continuous monitoring of air quality. In recent years, high levels of particulate matter (PM), including coarse (PM10) and fine (PM2.5) particles in the air have frequently been recorded. The aim of this study was to assess association between exacerbation of asthma or chronic obstructive pulmonary disease (COPD) in adults and air pollution or meteorological conditions. Methods. The study was conducted in the secondary care General Hospital in Smederevo covering approximately 81, 000 inhabitants living in the area of about 7 km around the automatic station for air quality monitoring from which the verified data were collected. Data on patients were obtained from medical records. The correlation between the incidence of diseases exacerbation and the number of days with exceedance of air pollutants limit level per month, as well as meteorological conditions, was tested with parametric Pearson bivariate correlation test in program SPSS. Results. The study population consisted of adults registered as asthma or COPD suffering patients (n = 1,624) with 570 episodes of remarkable exacerbations (moderate or severe) of the disease in 2011. Asthma exacerbation was significantly more frequent in women than in men. The number of days with high levels of PM2.5 per month was statistically significantly associated with the total number of exacerbation (moderate and severe of both asthma and COPD) episodes among the female patients. There was also a statistically significant association between the number of days with PM2.5 exceedance and the number of moderate exacerbations in the subgroups of non-smokers and obese patients. A significant correlation of the number of days with the exceedance of PM10 limit level was shown only for the subgroup of obese, non-smoking patients with moderate exacerbation. A significant negative association with the average ambient temperature was proven for the obese female patients and obese non-smoking patients with moderate asthma exacerbations. The number of COPD exacerbation was in positive correlation with the average air pressure for the subgroup of female smokers, but the connection with air pollution was not proven. Conclusion. Exposure to airborne particles in the town of Smederevo, mainly to PM2.5, and to low temperature may trigger asthma exacerbation requiring emergency care. The most vulnerable may be women and obese patients.